Contaminants in milk and impact of heating: An assessment study - Vandana Awasthi; Sanjivan Bahman; Lalit K Thakur; Santosh Kumar Singh; Ajit Dua; Sanjeev Ganguly (Wolters Kluwer Medknow Publications, 2012)
Background: The major contaminants usually encountered in milk and milk products include pesticide residues, heavy metals, and aflatoxin M1 (AFM1). Primarily, milk get contaminated before milching, from the cattle feed, from sources/materials used during the processing of milk as well as improper handling of the milk during the pre- and postprocessing period. Objective: The purpose of this study was to evaluate the effect of household practices on milk contaminants. Materials and Methods: Samples of pasteurized as well as unpasteurized milk (Vendor's milk) were analyzed for AFM1, pesticide residues, and heavy metals. Simulating the household practices, the impact of boiling on these contaminants was assessed. Results: The contaminant Aflatoxin M1 (AFM1) was detected at a concentration ranging from 0.071-0.075 ppb in unpasteurized as well as pasteurized milk samples analyzed during the course of study. Moreover, boiling had no impact on the quantity of AFM1 present in the milk. Pesticides and heavy metal contents were found to be within acceptable limits in all the milk samples tested. Conclusion: Mycotoxins especially aflatoxins in cattle feed and their consequential presence in milk and milk products is a serious concern world over as they are reported carcinogens. These fungal toxins are resistant to high temperatures and may lead to various health hazards. Preventive steps must be taken at each stage to ensure good quality of milk and milk products free from these contaminants. Awareness programs and education for the dairy farmers and milk processors may be helpful in this regard.